2005
DOI: 10.2174/1381612054864975
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Vancomycins and Related Antibiotics Against Infectious Diseases

Abstract: This review discusses the recent development of multivalent antibiotics as potential therapeutic agents against infections caused by antimicrobial drug resistant microbes. The discussion focuses on vancomycin because of its important clinical relevance and well-elucidated molecular mechanism of antimicrobial drug resistance. The first section recounts the increased occurrence of vancomycin resistance in the world; the second section briefly discusses the mechanistic study of vancomycin resistance; the third se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Multivalent strategy is originally based on these multivalent interactions, which has implications for design and use of multivalent ligands and inhibitors. Through the simultaneous recognition of multiple binding sites multivalent ligands can greatly enhance binding ability by several orders of magnitude in some cases (Rao et al 1998; Schaschke et al, 2001; Profit et al 1999) Covalently attaching bioactive compounds to a scaffold or core molecule has proven to be a successful strategy to greatly enhance the affinity of especially weak carbohydrate ligands to bind to bacteria toxins (Zhang et al 2002; Kitov et al 2000; Pukin et al 2007) and bacterial surfaces (Pieters 2007) The development of multivalent antibiotics (vancomycin) as a potential therapeutic agent against infections caused by drug resistant microbes such as methicillin-resistant staphylococcus aureus (MRSAs) is well documented, (Li and Xu 2005) and it shows the effectiveness of the multivalent strategy for the design of more effective anti-microbials. Multivalent AMPs can be formed by covalently linking to a scaffold or another core molecule.…”
Section: Design Principles For Multivalent Antimicrobial Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivalent strategy is originally based on these multivalent interactions, which has implications for design and use of multivalent ligands and inhibitors. Through the simultaneous recognition of multiple binding sites multivalent ligands can greatly enhance binding ability by several orders of magnitude in some cases (Rao et al 1998; Schaschke et al, 2001; Profit et al 1999) Covalently attaching bioactive compounds to a scaffold or core molecule has proven to be a successful strategy to greatly enhance the affinity of especially weak carbohydrate ligands to bind to bacteria toxins (Zhang et al 2002; Kitov et al 2000; Pukin et al 2007) and bacterial surfaces (Pieters 2007) The development of multivalent antibiotics (vancomycin) as a potential therapeutic agent against infections caused by drug resistant microbes such as methicillin-resistant staphylococcus aureus (MRSAs) is well documented, (Li and Xu 2005) and it shows the effectiveness of the multivalent strategy for the design of more effective anti-microbials. Multivalent AMPs can be formed by covalently linking to a scaffold or another core molecule.…”
Section: Design Principles For Multivalent Antimicrobial Peptidesmentioning
confidence: 99%
“…This hypothesis promoted synthetic chemists to design covalently-linked dimer or multivalent or polymeric forms of vancomycin (Arimoto et al 1999; Lu et al 2007). Arimoto et al, reported that the first multivalent polymer of vancomycin greatly enhanced its antimicrobial activity against vancomycin-resistant Enterococci (VRE, VanA and VanB) (Arimoto et al 1999; Li and Xu 2005). Polymeric forms of vancomycin (methanol) show the enhancement 8-63 fold in potency against VRE with retention of practical MIC values against S. aureus and Enterococci (Fig.…”
Section: Synthetic Unnatural Multivalent Ampsmentioning
confidence: 99%
“…Dimerization and ligand binding are cooperative in vancomycin and many related glycopeptide antibiotics 21, and it seems likely that the increased avidity of ligand recognition by the dimer enhances biological activity. This observation has prompted efforts to produce covalently-linked multivalent forms of the drug, in the hopes of developing variants of vancomycin with increased activity against vancomycin-resistant strains (reviewed in Li & Bu 22). Certain covalent dimers have been found to be significantly more potent against vancomycin-resistant enterococci (VRE) than is vancomycin itself 23–29.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of its prevalent use for the treatments of common clinical infections, Van-resistant bacteria, such as vancomycin-resistant Enterococcus faecium (VRE) strains, emerged as a serious threat to public health [4e7]. A typical mechanism of Van resistance is mutation of the pathogen peptidoglycan sequence from D-Ala-DAla to D-Ala-D-Lac, resulting in a significant decrease of the binding affinity to Van molecules [8]. Recent studies expounded the detailed structure and activity of Van toward the cell wall peptide analogues of drug resistant bacteria [9], and also noted that merely increasing the binding affinity of Van to the D-Ala-D-Lac peptide precursors might not lead to a substantial improvement of the minimum inhibitory concentration (MIC) value against these pathogens [10,11].…”
Section: Introductionmentioning
confidence: 99%